SENSITIVITAS ASPAL MODIFIKASI POLIMER SBS DAN ASPAL PEN 60/70 TERHADAP PERUBAHAN SUHU PEMADATAN PADA CAMPURAN HRS-WC DENGAN PENGUJIAN MARSHALL DAN PERMEABILITAS - , Mirza Prasetya K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The increase of the traffic growth in Indonesia in recent years has a high probability to become one of the causes of damaged road pavement. Various ways have been done to overcome these problems. One of them is the use of modified asphalt. This study used a synthetic elastomeric polymer modified asphalt called Styrene Butadiene Styrene (SBS) and pen asphalt 60/70 by using a mixture of Hot Rolled Sheet - Wearing Course (HRS-WC). The study was conducted to compare the characteristics of Marshall and permeability coefficient between these two types of asphalt mix. Polymer modified asphalt was expected to be used as one of the options to deal with damaged pavement. The research was carried out by making the specimen with compaction temperature variations: ToC, (T-10Â°C), and (T-20oC) where T was the compaction temperature standard (145oC for pen asphalt 60/70, 165oC for polymer modified asphalt). The tests performed were Marshall and permeability testing with compaction temperature variations. Sensitivity analysis was performed after each of the two tests for the asphalt to temperature changes compaction using one way ANOVA statistical analysis. HRS-WC mixtures using polymer modified asphalt had a better value of VMA, VITM, VFWA, stability, flow, and coefficient permeability than the pen asphalt 60/70. In line with the increasing of compaction temperature, coefficient of permeability increased, too. Permeability test results showed that both types of asphalt mixtures were included in the category of poor drainage. After the sensitivity of the compaction temperature variation against Marshall and permeability testing were analized, it was obtained that significance value was more than 0.05 for all test results, which means that both asphalt mixtures were not sensitive to the compaction temperature changes.